Association of suboptimal health status with psychosocial stress, plasma cortisol and mRNA expression of glucocorticoid receptor α/β in lymphocyte. (January 2015) - Yan, Yu-Xiang; Dong, Jing; Liu, You-Qin; Zhang, Jie; Song, Man-Shu; He, Yan; Wang, Wei
Abstract Suboptimal health status (SHS) has become a new public health challenge in China. This study investigated whether high SHS is associated with psychosocial stress, changes in cortisol level and/or glucocorticoid receptor (GR) isoform expression. Three-hundred eighty-six workers employed in three companies in Beijing were recruited. The SHS score was derived from data collection in the SHS questionnaire (SHSQ-25). The short standard version of the Copenhagen Psychosocial Questionnaire (COPSOQ) was used to assess job-related psychosocial stress. The mean value of the five scales of COPSOQ and distribution of plasma cortisol and mRNA expression of GRα/GRβ between the high level of SHS group and the low level of SHS group were compared using a general linear model procedure. Multiple linear regression analysis was used to analyze the effect of psychosocial stress on SHS. We identified three factors that were predictive of SHS, including "demands at work", "interpersonal relations and leadership" and "insecurity at work". Significantly higher levels of plasma cortisol and GRβ/GRα mRNA ratio were observed among the high SHS group. High level of SHS is associated with decreased mRNA expression of GRα. This study confirmed the association between chronic psychosocial stress and SHS, indicating that improving the psychosocial work environment may reduce SHS and then prevent chronic diseases effectively.